Pancasila in the Perspective of Customary Law in Indonesia - Marzuki, Abdul Ukas (Al-Bayyinah, 2024)
Harmonization between Pancasila and customary law in Indonesia, to identify the potential of customary law in strengthening Pancasila values in the context of the national legal system. This research uses a qualitative approach, collecting data through literature studies by searching various relevant literature, both in the form of books, scientific journals, and literature related to Pancasila and customary law in Indonesia. The results of the study show that there is harmony between the precepts of Pancasila and the values contained in customary law, especially in terms of togetherness, social justice, and respect for community life. However, there are still challenges in harmonization, such as the dominance of national law and the lack of formal recognition of customary law. Therefore, this article recommends several steps to achieve better harmonization, including formal recognition of the role of customary law, strengthening the capacity of customary law communities, and implementing deliberative dispute resolution mechanisms. This research emphasizes that customary law has a strategic role in strengthening the implementation of Pancasila values, so that it can contribute to a more equitable national development based on local wisdom.